2010
DOI: 10.1002/sia.3684
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized imidazolium wear‐resistant ionic liquid ultrathin films for MEMS/NEMS applications

Abstract: As a kind of new material, ionic liquids (ILs) are considered a new type of lubricant for micro/nanoelectromechanical system (M/NEMS) due to their excellent thermal and electrical conductivity. However, so far, only a few reports have investigated the friction and wear of thin films of these materials at the micro scale. Evaluating the nanoscale tribological performance of ILs when applied as films of a few nanometers thickness on a substrate is a critical step for their application in M/NEMS devices. To achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Zhu et al evaluated the friction of three imidazolium‐based ILs with the same cation and different anions and found that the anion impacts the friction significantly . Mo et al synthesized ILs of 1‐propyl‐3‐methylimidazolium with four different anions and then studied the nano‐ and micro‐ tribological properties of the IL films on silicon wafers using a friction force microscope (FFM) and a spherical probe and a UMT‐2MT tribotester . They found that the friction, adhesion and durability of IL thin films strongly depended on the structure of anions as well as wettability and ambient condition .…”
Section: Ionic Liquid Thin Films As Boundary Lubricantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al evaluated the friction of three imidazolium‐based ILs with the same cation and different anions and found that the anion impacts the friction significantly . Mo et al synthesized ILs of 1‐propyl‐3‐methylimidazolium with four different anions and then studied the nano‐ and micro‐ tribological properties of the IL films on silicon wafers using a friction force microscope (FFM) and a spherical probe and a UMT‐2MT tribotester . They found that the friction, adhesion and durability of IL thin films strongly depended on the structure of anions as well as wettability and ambient condition .…”
Section: Ionic Liquid Thin Films As Boundary Lubricantsmentioning
confidence: 99%
“…Mo et al synthesized ILs of 1‐propyl‐3‐methylimidazolium with four different anions and then studied the nano‐ and micro‐ tribological properties of the IL films on silicon wafers using a friction force microscope (FFM) and a spherical probe and a UMT‐2MT tribotester . They found that the friction, adhesion and durability of IL thin films strongly depended on the structure of anions as well as wettability and ambient condition . Zhao et al evaluated four ILs with the same cation and different anions on silicon wafer and reported that friction reduction, adhesion resistance and anti‐wear properties of ILs are largely dependent on the anions .…”
Section: Ionic Liquid Thin Films As Boundary Lubricantsmentioning
confidence: 99%
“…Several research groups have been testing the performance of different types of ILs as lubricants in tribological experiments with silicon wafers, aiming at a future application in MEMS/ NEMS. Most studies involve methylimidazolium based ILs, but there are also reports on pyridinium based ILs. [14–16] The effect of the anion on the tribological properties was investigated and, in particular, hexafluorophosphate, [PF 6 ], was considered to be the most promising .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several publications appeared in the literature reporting good tribological performance of sulfur‐based ILs,,, but the physico‐chemical reasons for this behaviour are still not clear. Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Surface textures and chemical modification are commonly used in magnetic data storage systems and microelectromechanical systems (MEMS) to reduce surface force to lessen the possibility of mechanical failure . A number of fabrication methods were used to generate micro/nano hierarchical structures for surface force control, including laser interface patterning, plasma/chemical etching, soft photolithography, sol–gel processing and solution casting, self‐assembled monolayers, electrical deposition, dip‐pen printing, and atomic force microscopy (AFM) local anodic oxidation, etc. Among the surface modification methods, the formation of self‐assembled monolayers (SAMs) proved to be a simple and economic technique for the adhesion control of solid surfaces.…”
Section: Introductionmentioning
confidence: 99%